Biologia populacional de Emerita brasiliensis Schmitt (Crustacea, Hippidae) na Praia Vermelha do Norte, Ubatuba (São Paulo, Brasil) - Nakagaki, Jelly Makoto (1999)
Emerita brasiliensis Schmitt, 1935 is a common mole crab called tatuíra in Brazil, with distribution from Espírito-Santo State (Brazil) to Buenos Aires Province (Argentina). Specimens were collected bimonthly from May/1992 through March/1993 with 4mm siffers mesh, in the intertidal region at Vermelha do Norte Beach, Ubatuba, São Paulo, Brazil. The animals were sexed and measured with a precision caliper of 0.1 mm (Cl = carapace length). Males presented cl amplitude from 3.4-17.3mm (13.2±2.1mm), and females from 13.8-26.3mm (20.5±1.8mm), showing a well-defined sexual dimorfism for this variable. The population presented a smaller incidence of males in relation to females (0.54:1.00), however in May/1992 an inverse pattern occurred (1.84:1.00). Ovigerous females were present in all samples with exception of May and September/1992 with greater frequencies in July/1992 and January/1993. It is probable that female maturity occurs is reached with 17mm CL, the smallest size in wich ovigerous females were found.